2019
DOI: 10.1126/science.aaw7515
|View full text |Cite
|
Sign up to set email alerts
|

Atomically dispersed Fe 3+ sites catalyze efficient CO 2 electroreduction to CO

Abstract: Currently, the most active electrocatalysts for the conversion of CO2 to CO are gold-based nanomaterials, whereas non–precious metal catalysts have shown low to modest activity. Here, we report a catalyst of dispersed single-atom iron sites that produces CO at an overpotential as low as 80 millivolts. Partial current density reaches 94 milliamperes per square centimeter at an overpotential of 340 millivolts. Operando x-ray absorption spectroscopy revealed the active sites to be discrete Fe3+ ions, coordinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
771
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,296 publications
(799 citation statements)
references
References 45 publications
(43 reference statements)
25
771
0
3
Order By: Relevance
“…The EXAFS is sensitive to the local structure without the need of long‐range order, thus it can provide information about the coordination number and bond distance of the SACs. The X‐ray photoelectron spectroscopy (XPS) can also reflect the oxidation states, chemical environments, and bonding information of the metal centers and its surrounding heteroatoms (e.g., N and S), which is usually used to supplement and support the results of XAS analysis . For Fe‐based SACs, the 57 Fe Mössbauer spectroscopy is a fingerprint technique that reflects the local electronic structure and coordination state of the Fe metal center .…”
Section: Coordination‐based Single Metal Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The EXAFS is sensitive to the local structure without the need of long‐range order, thus it can provide information about the coordination number and bond distance of the SACs. The X‐ray photoelectron spectroscopy (XPS) can also reflect the oxidation states, chemical environments, and bonding information of the metal centers and its surrounding heteroatoms (e.g., N and S), which is usually used to supplement and support the results of XAS analysis . For Fe‐based SACs, the 57 Fe Mössbauer spectroscopy is a fingerprint technique that reflects the local electronic structure and coordination state of the Fe metal center .…”
Section: Coordination‐based Single Metal Sitesmentioning
confidence: 99%
“…The type of coordinated N atoms is another factor to determine the oxidation states of the Fe center. In principle, the Fe 3+ ions are more active than Fe 2+ ions due to the enhanced CO 2 adsorption and CO desorption . The operando XAS technology showed that pyrrole‐type N promotes the stability of Fe 3+ more than Fe 2+ , while the pyridine‐type N has an opposite effect.…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis For mentioning
confidence: 99%
“…Copyright 2011, 2013 and 2018, Nature Publishing Group. Reproduced with permission . Copyright 2016, 2019 and 2012, American Association for the Advancement of Science (AAAS).…”
Section: Evolution From Nanoparticles Clusters To Single Atomsmentioning
confidence: 99%
“…Iron macrocyclic complexes are one of the most extensively researched categories of molecular catalysts for selective CO 2 reduction to CO . Because of the synthetic issues of such complexes, it is challenging to effectively immobilize them onto electrodes for practical application, which can be avoided by heterogeneous alternatives . A porous Fe 3 N single crystal was reported to yield CO with a selectivity of 90 % .…”
Section: Figurementioning
confidence: 99%
“…Singly dispersed FeN 5 active sites supported on N‐doped graphene enables CO 2 ‐to‐CO conversion with a FE of about 97.0 % . Recent study suggests that discrete Fe 3+ ions coordinated to pyrrolic nitrogen atoms of the N‐doped carbon support have ultrahigh activity for CO 2 electroreduction to CO . Compared with CO, alcohols possess advantages of higher energy density and easier storage at atmospheric pressure, and they are also widely used to feed the direct alcohols fuel cells .…”
Section: Figurementioning
confidence: 99%